Dampak Kompensasi terhadap Retensi Karyawan dengan Kepuasan Kerja sebagai Pemediasi - Bunga Dinda Hernawan; Veronika Agustini Srimulyani (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: The study aims to analyze the direct and indirect impact of compensation on employee retention with job satisfaction as a mediation. Research methodology: The study sample was 50 permanent employees of PT Daya Surya Sejahtera Ponorogo Regency. Data analysis includes data quality testing, classical assumptions, hypotheses. Hypothesis testing uses path analysis from hierarchical regression analysis. Results: Hypothesis testing results show that: 1) compensation has a positive significant effect on job satisfaction; 2) job satisfaction has a positive significant effect on employee retention; 3) compensation has a positive significant effect on employee retention; 4) job satisfaction acts as a full mediation indirect effect of compensation on employee retention. Limitations: The study focused on the direct and indirect impact of compensation on employee retention with job satisfaction as a mediation, and only on 50 permanent employees at one of the retail companies in Ponorogo district. Contribution: This finding proves that compensation for the form of appreciation given by the company to employees for employee contributions plays an important role in improving job satisfaction and employee retention in the company. This finding can be used as a development material for further research, especially the review of employee retention in retail businesses that are currently growing rapidly in Indonesia.